2015
DOI: 10.11648/j.sjph.20150305.38
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Free Medical Camps in Exposing Rural Communities' Dental Health Issues and Mitigating Morbidity Associated with Dental Caries

Abstract: Background:The study was conducted at IL-polei in Laikipia North, Kenya. The study aimed at determining the susceptibility to dental caries and oral health status, targeting children and teenagers between the ages of 3-17 years old attending a medical camp in the month of September in 2014. The study was designed as a community based cross-sectional descriptive study where questionnaires were administered to children, the guardians and parents of the children attending the dental section of the medical camp. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Through these camps, people can be educated on aspects like how and what to eat and drink, how and how long should they sleep, healthy recreational habits, and when to seek medical attention. Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] .…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%
“…Through these camps, people can be educated on aspects like how and what to eat and drink, how and how long should they sleep, healthy recreational habits, and when to seek medical attention. Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] .…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%